Utilization of community pharmacy space to enhance privacy: A qualitative study - Hattingh, H. Laetitia; Emmerton, Lynne; Ng Cheong Tin, Pascale; Green, Cathy (Blackwell Publishing Ltd, 2015)
© 2015 The Authors. Background: Community pharmacists require access to consumers' information about their medicines and health-related conditions to make informed decisions regarding treatment options. Open communication between consumers and pharmacists is ideal although consumers are only likely to disclose relevant information if they feel that their privacy requirements are being acknowledged and adhered to. Objective: This study sets out to explore community pharmacy privacy practices, experiences and expectations and the utilization of available space to achieve privacy. Methods: Qualitative methods were used, comprising a series of face-to-face interviews with 25 pharmacists and 55 pharmacy customers in Perth, Western Australia, between June and August 2013. Results: The use of private consultation areas for certain services and sensitive discussions was supported by pharmacists and consumers although there was recognition that workflow processes in some pharmacies may need to change to maximize the use of private areas. Pharmacy staff adopted various strategies to overcome privacy obstacles such as taking consumers to a quieter part of the pharmacy, avoiding exposure of sensitive items through packaging, lowering of voices, interacting during pharmacy quiet times and telephoning consumers. Pharmacy staff and consumers regularly had to apply judgement to achieve the required level of privacy. Discussion: Management of privacy can be challenging in the community pharmacy environment, and on-going work in this area is important. As community pharmacy practice is increasingly becoming more involved in advanced medication and disease state management services with unique privacy requirements, pharmacies' layouts and systems to address privacy challenges require a proactive approach.